Gymnopilus pholiotoides (Agaricales, Basidiomycota), an unexpected new record from an urban area in Brazil - Fabrini, Fernando; Guzmán-Dávalos, Laura; Wartchow, Felipe (Iheringia, Série Botânica., 2022)
Gymnopilus pholiotoides Murrill is discovered for the first time from Brazil. The Brazilian specimen is characterized by the orange tones then yellowish cream color in older basidiomes, pileus surface cracking into areolate appressed squamules when mature, presence of a fragile membranous pendant annulus, basidiospores (7.1–) 7.6–9.2 (–9.7) × 4.6–5.6 µm, absence of pleurocystidia, and presence of scattered caulocystidia. Description, discussion, drawings, and photographs of the sample are provided. Furthermore, a comparison with the type specimen of G. pholiotoides was made.